Enunciación, ficción y niveles semióticos en el texto narrativo - García Landa, José Ángel (Miscelánea: A Journal of English and American Studies, 1994)
This paper examines some conceptual connections between the areas of narratology and pragmalinguistics, with a specific focus on the enunciative peculiarities of fictional discourse. A descriptive model for semiotic analysis is proposed, taking into account the complex and stratified structure of narrative fiction and the difference between levels of enunciation and levels of fictionality.